The Interplay between Tubulins and P450 Cytochromes during Plasmodium berghei Invasion of Anopheles gambiae Midgut - Félix, Rute C. (Public Library of Science, 2011)
BACKGROUND: Plasmodium infection increases the oxidative stress inside the mosquito, leading to a significant alteration on transcription of Anopheles gambiae detoxification genes. Among these detoxification genes several P450 cytochromes and tubulins were differently expressed, suggesting their involvement in the mosquito's response to parasite invasion. P450 cytochromes are usually involved in the metabolism and detoxification of several compounds, but are also regulated by several pathogens, including malaria parasite. Tubulins are extremely important as components of the cytoskeleton, which rearrangement functions as a response to malaria parasite invasion. METHODOLOGY/PRINCIPAL FINDINGS: Gene silencing methods were used to uncover the effects of cytochrome P450 reductase, tubulinA and tubulinB silencing on the A. gambiae response to Plasmodium berghei invasion. The role of tubulins in counter infection processes was also investigated by inhibiting their effect. Colchicine, vinblastine and paclitaxel, three different tubulin inhibitors were injected into A. gambiae mosquitoes. Twenty-four hours post injection these mosquitoes were infected with P. berghei through a blood meal from infected CD1 mice. Cytochrome P450 gene expression was measured using RT-qPCR to detect differences in cytochrome expression between silenced, inhibited and control mosquitoes. Results showed that cytochrome P450 reductase silencing, as well as tubulin (A and B) silencing and inhibition affected the efficiency of Plasmodium infection. Silencing and inhibition also affected the expression levels of cytochromes P450. CONCLUSIONS: Our results suggest the existence of a relationship between tubulins and P450 cytochromes during A. gambiae immune response to P. berghei invasion. One of the P450 cytochromes in this study, CYP6Z2, stands out as the potential link in this association. Further work is needed to fully understand the role of tubulin genes in the response to Plasmodium infection.